Examining the Relationship Between Innovation Characteristics and Extension Support When Using Jajar Legowo as an Agricultural Innovation - Putra, Rizki Aditya; Sadono, Dwi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
The Jajar Legowo, as an agricultural technique innovation, has been introduced to farmers in Pangkal Jaya Village for quite some time. However, its implementation has not consistently followed the recommendations despite its proven ability to increase rice production. This research aims to review the adoption of the